Effect of Blockage of the Ducts of the Vomeronasal Organ on LH Plasma Levels during the “Whitten Effect” in Does - Kenneth Kurt Booth; Edward Cottington Webb (Veterinary Medicine International)
Eighteen mature, nonpregnant, and indigenous South African does were randomly divided into two groups to test if their vomeronasal organs exert an influence on LH plasma levels during a Whitten effect experimental trial. Does in the treatment (VNO ablated) group had their vomeronasal organs rendered nonfunctional by cauterization of the nasoincisive duct under surgical anesthesia. Does in the control group had their nasal civities irrigated with physiological saline under surgical anesthesia. All does were synchronized into oestrus and introduced to bucks one day prior to their expected second oestrus cycle. Successful matings were recorded. Timely blood samples were collected during each of the five days before and five days after buck introduction. Blood plasma concentrations of estradiol and LH were determined by radioimmunoassay. Analysis of variance between groups demonstrated that the does in the VNO ablated group did not demonstrate any interest in mating, did not become pregnant, and did not demonstrate the primary increase in tonic plasma levels of LH that is necessary for ovulation to occur. By contrast, all of the does in the control group demonstrated successful matings, became pregnant, and demonstrated typical primary tonic level increases and preovulation surges in LH. Thus, it was concluded that the vomeronasal organ modulates the primary increase in tonic levels of LH and thus influences ovulation that occurs during the Whitten effect in South African indigenous does.